Objectively measured physical activity in patients with COPD: recommendations from an international task force on physical activity. - Demeyer,H; Mohan,D; Burtin,C; Vaes,AW; Heasley,M; Bowler,RP; Casaburi,R; Cooper,CB; Corriol-Rohou,S; Frei,A; Hamilton,A; Hopkinson,NS; et al. (COPD: Journal of Chronic Obstructive Pulmonary Disease, 2021)
Physical activity (PA) is of key importance for health among healthy persons and individuals with chronic obstructive pulmonary disease (COPD). PA has multiple dimensions that can be assessed and quantified objectively using activity monitors. Moreover, as shown in the published literature, variable methodologies have been used to date to quantify PA among individuals with COPD, precluding clear comparisons of outcomes across studies. The present paper aims to provide a summary of the available literature for the rationale behind using objectively measured PA and proposes a standardized methodology for assessment, including standard operating procedures for future research. The present paper, therefore, describes the concept of PA, reports on the importance of PA, summarizes the dimensions of PA, provides a standard operating procedure on how to monitor PA using objective assessments, and describes the psychometric properties of objectively measured PA. The present international task force recommends implementation of the standard operating procedure for PA data collection and reporting in the future. This should further clarify the relationship between PA and clinical outcomes, test the impact of treatment interventions on PA in individuals with COPD, and successfully propose a PA endpoint for regulatory qualification in the future.